Potencial mirmecológico na vetoração mecânica de helmintos em gatis - Machado, J. C.; Brugger, M. S. [UNESP]; Souza, J. O. T.; Lopes, J. F. S. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2011)
Vector potential of ants in mechanic dissemination of helminthes in a cat rescue center was analyzed in this study. Ants walking over cat's food and feces were collected and conditioned in distilled water. Cat feces were collected too. Ants were identified and the water where they were conditioned was observed on optic microscope. It was made the simple sedimentation technique to analyze feces. The results show that ants species Pheidole and Paratrechina can be potential vectors of nematode eggs, mainly Ascaridida, Toxocaridae.
Myrmecological potential in mechanic vectoring of helminthes in cats rescue center
Keywords: ant; cat; parasites; vector